Transcriptional Heterogeneity in Naive and Primed Human Pluripotent Stem Cells at Single-Cell Resolution - Messmer, Tobias (Cell Rep, 2019)
Conventional human embryonic stem cells are considered to be primed pluripotent but can be induced to enter a naive state. However, the transcriptional features associated with naive and primed pluripotency are still not fully understood. Here we used single-cell RNA sequencing to characterize the differences between these conditions. We observed that both naive and primed populations were mostly homogeneous with no clear lineage-related structure and identified an intermediate subpopulation of naive cells with primed-like expression. We found that the naive-primed pluripotency axis is preserved across species, although the timing of the transition to a primed state is species specific. We also identified markers for distinguishing human naive and primed pluripotency as well as strong co-regulatory relationships between lineage markers and epigenetic regulators that were exclusive to naive cells. Our data provide valuable insights into the transcriptional landscape of human pluripotency at a cellular and genome-wide resolution.